Review of Optical Diagnostic Technique for Diesel Spray - Ihwan Ghazali; La Ode Mohammad Firman; Handi; Yusrizal; Ayu Amanah; Mohammed Bashir Abdulrahman (The Indonesian Institute of Science and Technology Research, 2022)
To enhance the fuel efficiency and reduce both NOX and soot emissions in diesel engine, it is essential to understand the mixture formation and the combustion process in the cylinder. The injection parameters such as pressure, mass and multiple approaches as well as the impingement play an important role in mixture formation, combustion process and emissions. Previous works have addressed various optical diagnostic techniques. This review describes those factors mentioned above systematically to clarify the diesel spray in the compression ignition engine. Therefore, a diesel vehicle with better fuel economy and low emission that meets the stringent regulation across the world could be realized.